2019
DOI: 10.1371/journal.pone.0212128
|View full text |Cite
|
Sign up to set email alerts
|

Globally important islands where eradicating invasive mammals will benefit highly threatened vertebrates

Abstract: Invasive alien species are a major threat to native insular species. Eradicating invasive mammals from islands is a feasible and proven approach to prevent biodiversity loss. We developed a conceptual framework to identify globally important islands for invasive mammal eradications to prevent imminent extinctions of highly threatened species using biogeographic and technical factors, plus a novel approach to consider socio-political feasibility. We applied this framework using a comprehensive dataset describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 42 publications
4
110
0
Order By: Relevance
“…Invasive species represent one of the greatest management challenges facing insular biota globally [57, 58]. Our synthesis builds on a body of literature showing that the presence of non-native species in the context of altered landscapes and growing human populations is not a new phenomenon; rather, the predisposition of certain insular ecosystems to the effects of modern invasive species may be undergirded by their unique accumulated histories of Indigenous and colonial activity, demanding inclusion of paleontological and archaeological knowledge in conservation planning [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive species represent one of the greatest management challenges facing insular biota globally [57, 58]. Our synthesis builds on a body of literature showing that the presence of non-native species in the context of altered landscapes and growing human populations is not a new phenomenon; rather, the predisposition of certain insular ecosystems to the effects of modern invasive species may be undergirded by their unique accumulated histories of Indigenous and colonial activity, demanding inclusion of paleontological and archaeological knowledge in conservation planning [56].…”
Section: Resultsmentioning
confidence: 99%
“…If the goal is to maintain the status quo of insular biodiversity and protect still-surviving endemic species, eradication of non-native species represents the most significant gain for island endemics [57]. A global analysis of insular systems indicated that the Caribbean has a large proportion of biologically important islands (45 of 292, or 15.4%) where eradication would be beneficial [58]. Ongoing eradications of Rattus from small islands used heavily by seabirds may have positive ecological effects on nutrient cycling [59].…”
Section: Introductionmentioning
confidence: 99%
“…An important future output is a priority list, ranking Mediterranean islands in terms of cost‐effectiveness of invasive mammal eradication and comparing benefits to the monetary costs, as has already been done for other contexts on a different scale (e.g. Brooke et al , Capizzi et al , Holmes et al ). Prioritising conservation actions can be a strategic tool and a useful guide for managers, conservationists, and politicians, allowing them to convey limited resources to the worthiest restoration projects (Wilson et al , Helmstedt et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the critical size of the sole existing population of Niau kingfishers, it is important to avoid any additional mortality due to key prey rarefaction (or even direct preda-tion). For these reasons, Niau Island was recently listed amongst islands worldwide where introduced mammal eradications are required to prevent imminent extinction of endemic vertebrates (Holmes et al 2019).…”
Section: Conclusion and Conservation Perspectivesmentioning
confidence: 99%